Die südlichen Osterseen bei Iffeldorf in Oberbayern.: Luftbildinterpretation einer Jungglaziallandschaft - Bodechtel, Johann (ERDKUNDE, 1965)
Using as example the Oster lake area, the relief of which is due to the disintegration of the Quaternary ice sheet, the paper demonstrates the applicability of geomorphological interpretation of air photographs for identifying glacial deposits. Photo-geological analysis facilitates their immediate classification. Various glacial landforms which are frequently only distinguishable on an morphological basis, such as aser, drumlins, kames and kettleholes, can thus be mapped with a degree of precision hardly attainable in field mapping.